TAFRO Syndrome Without Pathology Supporting Castleman Disease: To Be Treated as Idiopathic Multicentric Castleman Disease-TAFRO or a Distinct Disease Entity? - Siyuan Li; Yuhan Gao; Yue Dang; Lu Zhang; Jian Li (Turkish Journal of Hematology, 2025)
Objective: TAFRO syndrome, entailing thrombocytopenia, anasarca, fever, reticulin fibrosis, and organomegaly, was previously considered a subtype of idiopathic multicentric Castleman disease (iMCD-TAFRO), with the diagnosis requiring pathology supporting Castleman disease. However, lymph node biopsies may be difficult for TAFRO patients (TAFRO without pathological evidence: TAFRO-w/op-iMCD), and sometimes these biopsies do not confirm iMCD (TAFRO-w/o-iMCD). We aimed to compare the clinical features and prognosis of TAFRO subgroups. Materials and Methods: We retrospectively analyzed the cases of 50 iMCD-TAFRO and 11 TAFRO-w/o-iMCD patients treated from May 2015 to April 2024. Results: The groups showed no significant differences in clinical presentation or laboratory data. Both groups of patients were treated with iMCD-targeted strategies addressing cytokine storms. With a median follow-up of 21.4 (range: 0.5-107.0) months, there were no significant differences between iMCD-TAFRO and TAFRO-w/o-iMCD patients in 3-month response rate (72.1% vs. 88.9%, p=0.525), 6-month response rate (70.0% vs. 83.3%, p=0.849), or best overall response rate (77.6% vs. 90.0%, p=0.645). The estimated 3-year progression-free survival rate (65.8% vs. 90.0%, log-rank p=0.163) and the estimated 3-year overall survival rate (77.0% vs. 100%, log-rank p=0.145) were also not significantly different. Cox univariate analysis showed that decreased estimated glomerular filtration rate (<60 mL/min/1.73 m2) was associated with an increased risk of disease progression (hazard ratio: 4.133, 95% confidence interval: 1.561-10.940, p=0.004). Conclusion: iMCD-TAFRO and TAFRO-w/o-iMCD could be considered overlapping entities and these patients should be treated promptly, targeting cytokine storms with similar strategies for each group of patients.